AMP-Activated Protein Kinase and O-GlcNAcylation, Two Partners Tightly Connected to Regulate Key Cellular Processes - Gélinas, Roselle; Dontaine, Justine; Horman, Sandrine; Beauloye, Christophe; Bultot, Laurent; Bertrand, Luc (Frontiers in Endocrinology, 2018)
The AMP-activated protein kinase (AMPK) is an important cellular energy sensor. Its activation under energetic stress is known to activate energy-producing pathways and to inactivate energy-consuming pathways, promoting ATP preservation and cell survival. AMPK has been shown to play protective role in many pathophysiological processes including cardiovascular diseases, diabetes and cancer. Its action is multi-faceted and comprises short-term regulation of enzymes by direct phosphorylation as well as long-term adaptation via control of transcription factors and cellular events such as autophagy. During the last decade, several studies underline the particular importance of the interaction between AMPK and the post-translational modification called O-GlcNAcylation. O-GlcNAcylation means the O-linked attachment of a single N-acetylglucosamine moiety on serine or threonine residues. O-GlcNAcylation plays a role in multiple physiological cellular processes but is also associated with the development of various diseases. The first goal of the present review is to present the tight molecular relationship between AMPK and enzymes regulating O-GlcNAcylation. We then draw the attention of the reader on the putative importance of this interaction in different pathophysiological events.